The Relationship Between Anxiety Levels, Sleep, and Physical Activity During COVID-19 Lockdown: An Exploratory Study - Frontini, Roberta; Rebelo-Gonçalves, Ricardo; Amaro, Nuno; Salvador, Rogério; Matos, Rui; Morouço, Pedro; Antunes, Raul (Frontiers in Psychology, 2021)
Nowadays and worldwide the attention is focused on coronavirus disease (COVID-19), and its consequences on mental health are yet to be fully understood. It is important to capture differences in anxiety levels among populations, groups and the gender-related variation. Therefore, the present study had two main purposes: 1) to characterize the levels of state-anxiety and trait-anxiety by examining gender-related, sleep-related and physical activity-related variation in a non-representative sample of the Portuguese population during the first weeks of lockdown and; 2) to explore the possible relationship between trait-anxiety and state-anxiety and the possible role of gender as a moderator. This cross-sectional study comprised 1332 Portuguese adults (aged 18-55 years old), recruited online during COVID-19 outbreak measures. Participants answered to socio-demographic data and the Portuguese version of the State-Trait Anxiety Inventory (STAI). Gender differences were found in both state-anxiety (p=<0.001; d=0.385) and trait-anxiety (p=<0.001; d=0.467) with females presenting higher values. People reporting doing more physical activity than usual during COVID-19 lockdown presented lower levels of state-anxiety (p=<0.001; d=0.200). People reporting more satisfaction with the quality of sleep presented lower levels of both state-anxiety (p=<0.001; d=0.701) and trait-anxiety (p=<0.001; d=0.899). Variation associated with physical activity level (low, moderate, and high) was significantly different among groups in both state-anxiety (p=<0.001) and trait-anxiety (p=<0.001). When analyzing in more detail separating the levels of physical activity, participants performing moderate and high physical activity showed lower values of state and trait anxiety compared to participants with low physical activity. Participants performing high physical activity also showed lower values of state-anxiety compared to participants performing moderate physical activity. Higher levels of trait-anxiety were related to higher levels of state-anxiety, but this association was not moderated by gender. Interventions aiming to support people psychologically during this outbreak should consider anxiety as well as gender and possible behavioral changes in sleep and physical activity, for example Health professionals should not only consider the anxiety related to the situation we are living but also address trait-anxiety to help overcome COVID-19 psychological consequences.